Acetylation-dependent nuclear arrangement and recruitment of BMI1 protein to UV-damaged chromatin - Sustáčková, Gabriela; Kozubek, Stanislav; Stixová, Lenka; Legartová, Soňa; Matula, Pavel; Orlova, Darya; Bártová, Eva (Journal of cellular physiology, 2012)
Polycomb group (PcG) proteins, organized into Polycomb bodies, are important regulatory components of epigenetic processes involved in the heritable transcriptional repression of target genes. Here, we asked whether acetylation can influence the nuclear arrangement and function of the BMI1 protein, a core component of the Polycomb group complex, PRC1. We used time-lapse confocal microscopy, micro-irradiation by UV laser (355 nm) and GFP technology to study the dynamics and function of the BMI1 protein. We observed that BMI1 was recruited to UV-damaged chromatin simultaneously with decreased lysine acetylation, followed by the recruitment of heterochromatin protein HP1β to micro-irradiated regions. Pronounced recruitment of BMI1 was rapid, with half-time τ = 15 sec; thus, BMI1 is likely involved in the initiation step leading to the recognition of UV-damaged sites. Histone hyperacetylation, stimulated by HDAC inhibitor TSA, suppression of transcription by actinomycin D, and ATP-depletion prevented increased accumulation of BMI1 to γH2AX-positive irradiated chromatin. Moreover, BMI1 had slight ability to recognize spontaneously occurring DNA breaks caused by other pathophysiological processes. Taken together, our data indicate that the dynamics of recognition of UV-damaged chromatin, and the nuclear arrangement of BMI1 protein can be influenced by acetylation and occur as an early event prior to the recruitment of HPβ to UV-irradiated chromatin.
Keywords: kyseliny hydroxamové; chromatin; poškození DNA; Chromatin; konfokální mikroskopie; Fluorescence Recovery After Photobleaching; Chromosomal Proteins, Non-Histone; zelené fluorescenční proteiny; Animals; Polycomb-Group Proteins; FRAP; Polycomb Repressive Complex 1; homolog proteinu s chromoboxem 5; histony; represorové proteiny; Humans; Mice; DNA Damage; Hydroxamic Acids; Microscopy, Confocal; Time-Lapse Imaging; chromozomální proteiny, nehistonové; polycomb proteiny; inhibitory histondeacetylas; Ultraviolet Rays; Cell Line; PRC1; rekombinantní fúzní proteiny; Histone Deacetylase Inhibitors; zvířata; 3T3 Cells; Chromobox Protein Homolog 5; časosběrné zobrazování; ultrafialové záření; Green Fluorescent Proteins; jaderné proteiny; Acetylation; Histones; acetylace; Nuclear Proteins; Recombinant Fusion Proteins; Repressor Proteins; lidé; protoonkogenní proteiny; Proto-Oncogene Proteins; buněčné linie; buňky 3T3; myši